ANALISIS KEMAMPUAN VOCABULARY MAHASISWA PRODI KESEHATAN MASYARAKAT DALAM MATA KULIAH ENGLISH PRACTICE - Nurdin, Hidayanti Rohimah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Mastery of vocabulary is the first step to be able to communicate in English, it is important to learn vocabulary in learning a foreign language. This study aims to see the extent of public health study program students' vocabulary knowledge in fourth semester in several themes of English practice courses. The research method was carried out using qualitative descriptive research with a total of 30 respondents. The results of the study found that the level of students' vocabulary knowledge for theme kind of drug and medical herb wer categorized as sufficient, and vocabulary knowledge for bulimia nervosa and ebola epidemic theme were categorized as insufficient. It is recommended for english practice lecturers to use more creative and varied methods to increase student interest in the learning process.